Grundtvigs prædiken i Vartov 1. maj 1844 - Holm, Jette; Glenthøj, Elisabeth Albinus (Grundtvig-Studier, 2005)
Grundtvigs prædiken i Vartov 1. maj 1844 [Grundtvig’s sermon in Vartov, 1 May 1844] By Jette Holm and Elisabeth A. Glenthøj On Wednesday 1 May 1844 Grundtvig, ill from an attack of mumps and attendant depression, preached his last sermon before setting out on a convalescence visit to clerical friends in Sjælland. The sermon, hitherto unprinted, is presented here to supplement Christian Thodberg’s study of the remarkable process by which Grundtvig’s Sov sodt, Barnlille was begotten out of the interaction of personal crisis, sermon, biblical text and liturgy. It also offers a sample of the sermons from Vartov currently being issued. The first three volumes (sermons 1839-42), plus a volume of commentary, were published in 2003 by Forlaget Vartov; and the next instalment with three annual sets of sermons (1843-45), plus commentary, are expected to be ready for printing in Spring 2006.